Discourse of religious pluralism in Indonesia - Thoha, Anis Malik (2011)
In Indonesia, which is a multi-cultural and multi-religious country, inter-group conflicts frequently take place in religious forms and colours, or involve religious issues directly. Many, accordingly, have attempted to propose the concept and theory of “religious pluralism” in order to provide a peaceful and humane solution to the problem. Soeharto’s government has been regarded as the most systematic and successful institution in dealing with religious conflicts. At least, it managed, to a large extent and by any means, to control and to stop these conflicts from bursting. However, as soon as this regime collapsed in 1998, the religious conflicts came into existence on a large scale in different parts of the country, such as in Moluccas and Poso, Eastern Indonesia. Therefore, in the era of “reformation”, the discourse of religious pluralism gains currency – and moral acknowledgement – more than before, within the different levels and circles of society in Indonesia.